The Houthi Movement (Ansar Allah) Facing the Coalition Forces - Alogai, Fikri (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2015)
The unrest prevailed in the Arab world during and after the Arab Spring and the escalation of the rivalry between Iran and Saudi Arabia made all parties feel reluctant to make concessions to reach a settlement. The challenge for the Yemeni negotiators is to find a path to stop the escalation, despite the outbreak of fighting in several places. The local parties, which would be the big¬gest loser, should be supported to reach some agreement. This is because a proxy war which is sectarian in nature will not create victors. Thus a political settlement would be less costly to achieve reasonable goals. Ideally, escalation could occur through a cease-fire mediated and watched by the Security Council. Then negotiations under the auspices of the United Nations and with the support of the GCC could be resumed to reach a settlement on the most pivotal issue: the executive authority. A GCC, especially Saudi Arabia, could help settlement by encouraging Hadi to accept a minimum collective leadership. An even better solution is for Hadi to resign to reach an ac¬ceptable agreement on a large scale for the establishment of an executive authority. The Sultanate of Oman, being more neutral could to be a potential place for the negotiations; it would be even good to assist in managing the negotiation If the parties were able to settle the issue of the presidency and stop the escalation, Yemenis can move then to negotiate details about power-sharing before the election and put a framework to address the state structure. The progress that has been made already in negotiations indicates there is a possibility for a reasonable solution.

Niepokoje, które rozlały się po świecie arabskim w czasie i po wydarzeniach określanych mianem Arabskiej wiosny, a także rywalizacja między Iranem i Arabią Saudyjską spowodowały, że wszystkie strony stały się niechętne porozumieniu. Wyzwanie dla jemeńskich negocjatorów stanowi znalezienie drogi pozwalającej na powstrzymanie eskalacji konfliktu. Dążąc do osiągnięcia porozumienia należy wspierać lokalne siły, a samo porozumienie uznać za najlepszy sposób osiągnięcia celów. Scenariusz zakłada zawieszenie ognia nadzorowane przez Radę Bezpieczeństwa ONZ, a następnie negocjacje przy jednoczesnej mediacji Narodów Zjednoczonych i Rady Współpracy Zatoki, ze szczególną rolą Arabii Saudyjskiej, której władze byłyby w stanie przekonać przedstawicieli Hadi do zawarcia porozumienia. Oman, jako państwo podkreślające swą neutralność w toczącym się konflikcie - mógłby pełnić dobre usługi, udzielając miejsca pod rozmowy. Wszystko po to, aby uzgodnić kwestię prezydentury, a w dalszej kolejno¬ści podział władzy i nowe zasady funkcjonowania państwa.
Ruch Huti a siły koalicyjne